Relationship between levels of nutrients and habitual coffee consumption and the incidence of anemia in former leprosy patients - Ginting, Sadar; Sidabutar, Sondang; Renaldi Sihombing, Eka Saudur (International Journal Of Community Medicine And Public Health, 2018)
Background: Former leprosy patients are a group of people that are at risk of anemia. Anemia in the former leprosy can be caused by daily food consumption and coffee drinking behavior. This study aimed is to determine the relationship between the levels of nutrients and habitual coffee consumption and the incidence of anemia in the former leprosy patients. Methods: Design of this study is cross sectional. There were 115 former leprosy patients, all of whom were selected as subjects for this study. The nutrient consumption data were obtained through filling out 24-hour food recall forms; the coffee drinking habit was obtained through questionnaire; and the incidence of anemia were obtained through Hb level examination by using Digital Acute Check. The data obtained were analyzed with Chi-Square statistical test and binary logistic regression. Results: Protein intake (p value 0.003), iron intake (p value 0.001), and habitual coffee consumption (p value 0.035) have significant relationship with the incidence of anemia. While energy intake (p value 0.833) and Vit. C intake (p value 0.516) have no significant relationship with the incidence of anemia in former leprosy patients. Iron intake is a dominant factor affecting the occurrence of anemia in former leprosy patients. Conclusions: Nutrient consumption is lower than the recommended dietary allowance, especially iron. The daily coffee consuption can inhibit iron absorption. Thus, it appears that insufficient levels of protein and iron, and the consumption of coffee are the factors that affect the occurrence of anemia in the former leprosy patients.